How patient acceptability affects access to breast reconstruction: a qualitative study - Nancy N Baxter; Helene Retrouvey; Fiona Webster (BMJ Open)
Objectives There has been limited research on the acceptability of breast reconstruction (BR) to breast cancer patients. We performed interviews to explore breast cancer patients’ acceptability of BR.Design Qualitative study.Setting Recruitment from six Ontario hospitals across the province (Toronto, Ottawa, Hamilton, London, Thunder Bay and Windsor) as well as key breast cancer organisations between November 2017 and June 2018.Participants Women of any age with a diagnosis of breast cancer planning to undergo or having undergone a mastectomy with or without BR.Intervention Sixty-minute semi-structured interviews were analysed using qualitative descriptive methodology that draws on inductive thematic analysis.Outcome In the telephone interviews, participants discussed their experience with breast cancer and accessing BR, focusing on the acceptability of BR as a surgical option post-mastectomy.Results Of the 28 participants, 11 had undergone BR at the time of the interview, 5 at the time of mastectomy and 6 at a later date. Four inter-related themes were identified that reflected women’s evolving ideas about BR as they progressed through different stages of their disease and treatment. The themes we developed were: (1) cancer survival before BR, (2) the influence of physicians on BR acceptability, (3) patient’s shift to BR acceptance and (4) women’s need to justify BR. For many women, access to BR surgery became more salient over time, thus adding a temporal element to the existing access framework.Conclusion In our study, women’s access to BR was negatively influenced by the poor acceptability of this surgical procedure. The acceptability of BR was a complex process taking place over time, from the moment of breast cancer diagnosis to BR consideration. BR access may be improved through enhancing patient acceptability of BR. We suggest adapting the current access to care frameworks by further developing the concept of acceptability.